Communal Attitudes on English Educational Tourism in Eastern Indonesia - Muhammad Basri; Muhammad Azwar Paramma; Andi Hudriati; Desy Satriyani Tamrin (Universitas Negeri Makassar, 2022)
English educational tourism (EET) is a new breakthrough in the tourism industry in eastern Indonesia, carrying the concept of a global village to promote economic development, education, and tourism. Research on this topic has been well documented in the literature; however, it is necessary to understand the communal attitudes from a local community perspective. It seeks to explore the public’s perception of this innovation based on three dimensions of attitude: (affective, behavioral, and cognitive). This study employed an exploratory case study through an online self-perception survey and interviews with the local communities. Data generated from the online survey and focus group interviews were analyzed using thematic analysis. As a result, the study found that local communities have positive emotions (thoughts and feelings) towards the global village initiative and generally believe that it will bring significant contributions to the local communities’ economic growth, education, and tourism. Thus, they will participate and take necessary actions to promote the village in the global societies. This program will enhance community economic growth, English immersion education, and the tourism industry in eastern Indonesia. In other words, this village will catalyze the growth of small and medium enterprises (SMEs) in the hospitality industries, such as transportation, accommodation, recreation, and food and beverage businesses.